CD49f is an efficient marker of monolayer- and spheroid colony-forming cells of the benign and malignant human prostate. - Hidekazu Yamamoto; John R Masters; Prokar Dasgupta; Ashish Chandra; Rick Popert; Alex Freeman; Aamir Ahmed (PLoS ONE)
Stem cells may play a role in the development and maintenance of proliferative diseases of the prostate such as prostate cancer and benign prostatic hyperplasia. Cell membrane protein markers, CD49f, CD133 and CD44, have been shown to identify putative prostate stem cells, but a lack of consensus exists with regards to the most efficient marker(s) for stem-like cell identification. This study aimed to determine whether previously reported markers had equal capacity to select monolayer and spheroid colony-forming cells (CFCs), which were used as surrogate readouts of stem-like cells, and to characterize the expression of CD49f, CD44 and CD133 by flow cytometry and immunohistochemistry.In benign prostate cells, CD49f+, CD44+, and CD133+ cells represented 5.6±3.1%, 28.2±4.1% and 0.10±0.06% of total cells. Both monolayer- and spheroid-CFCs existed at a frequency of approximately 0.5% of total cells. CD49f+, CD44+, and CD133+ subpopulations differed significantly in their ability to select benign CFCs. The highest recovery of CFCs was achieved by CD49f+ selection (98%), whereas CD44+ or CD133+ selection led to poor CFC-recovery (17% and 3%, respectively). For the first time, we show highly efficient recovery of CFCs from advanced prostate cancer by CD49f+, but not by CD44+ or CD133+ selection. Furthermore, CD133 expression (AC133 clone) could not be detected in benign prostate cells by either immunohistochemistry or flow cytometry. We conclude that CD49f, but not previously described stem cell markers CD133 and CD44, to be optimal for selection of monolayer- and spheroid-CFCs in the benign and malignant prostate.